Acylation, a Conductor of Ghrelin Function in Brain Health and Disease - Thomas, Alanna S.; Sassi, Martina; Angelini, Roberto; Morgan, Alwena H.; Davies, Jeffrey S. (Frontiers in Physiology, 2022)
Acyl-ghrelin (AG) is an orexigenic hormone that has a unique octanoyl modification on its third serine residue. It is often referred to as the “hunger hormone” due to its involvement in stimulating food intake and regulating energy homeostasis. The discovery of the enzyme ghrelin-O-acyltransferase (GOAT), which catalyses ghrelin acylation, provided further insights into the relevance of this lipidation process for the activation of the growth hormone secretagogue receptor (GHS-R) by acyl-ghrelin. Although acyl-ghrelin is predominantly linked with octanoic acid, a range of saturated fatty acids can also bind to ghrelin possibly leading to specific functions. Sources of ghrelin acylation include beta oxidation of longer chain fatty acids, with contributions from fatty acid synthesis, the diet, and the microbiome. Importantly, acyl-ghrelin can be de-acylated into unacylated-ghrelin (UAG) by acyl-protein thioesterase 1 (APT1) and buturylcholinesterase (BChE), allowing for cell specific modulation of GHS-R activity. In addition, both acyl-ghrelin and UAG have feedback effects on lipid metabolism which in turn modulate their levels. Recently we showed that whilst acyl-ghrelin promotes adult hippocampal neurogenesis and enhances memory function, UAG inhibits these processes. As a result, we postulated that the circulating acyl-ghrelin:unacylated-ghrelin (AG:UAG) ratio might be an important regulator of neurogenesis and cognition. In this review, we discuss emerging evidence behind the relevance of ghrelin acylation in the context of brain physiology and pathology, as well as the current challenges of identifying the provenance of the acyl moiety.